Characterisation of Multiparametric Magnetic Resonance Imaging of the Prostate in Younger Men with Normal Prostate-specific Antigen Within the PROBASE Study - Rouvier Al-Monajjed; Lars Schimmöller; Jan Philipp Radtke; Jale Lakes; Agne Krilaviciute; Heinz-Peter Schlemmer; Kathleen Herkommer; Petra Seibold; Nikolaus Becker; Rudolf Kaaks; Boris Hadaschik; Gerald Antoch; et al. (European Urology Open Science)
Background and objective: Multiparametric magnetic resonance imaging (mpMRI) has emerged as an essential tool for the diagnosis of prostate cancer (PC). However, the right time to start screening for PC is not defined. This study aims to analyse mpMRI in young men at the age of 47–52 yr with normal prostate-specific antigen (PSA) values of ≤3 ng/ml. Methods: In this prospective analysis, consecutive men undergoing PSA screening with PSA levels below 3 ng/ml were offered mpMRI as part of the PROBASE study. Magnetic resonance imaging (MRI) parameters were assessed, and the findings included changes in T2-weighted (T2w) images, apparent diffusion coefficient (ADC), and dynamic contrast enhancement (DCE). Prostate Imaging Reporting and Data System (PI-RADS) category 4 or 5 would indicate a biopsy. The Kruskal-Wallis test was used to compare the ADC and PSA values across different PI-RADS categories, and the Spearman rho test was used to examine the relationship between T2w changes and PSA values for PI-RADS categories. Key findings and limitations: Forty-seven men were included (median PSA 1.22 ng/ml; interquartile range 0.47–1.79 ng/ml) between September 2021 and March 2022. High-quality MRI (median Prostate Imaging Quality [PI-QUAL] score 5) resulted in a median PI-RADS classification of 2 with low prostate volumes (median 27 ml). PI-RADS 3 classification occurred in 45% (median PSA 1.51 ng/ml). No score higher than PI-RADS 3 was observed. After 2-yr follow-up, no PC was reported in these men. For the peripheral zone (PZ), diffuse T2w changes were present in 81%. Focal and accentuated T2w changes were detected in 11% and 40%, respectively. DCE of the PZ was observed partially and severely in 53% and 17%, respectively. Limitations of this study are its small sample size, which provides more uncertainty regarding whether we were able to find reliable estimates for the outcomes explored in this study, the single-centre design, and the limited histopathological proof of nonmalignant cases. Conclusions and clinical implications: In younger men with normal PSA levels, clinically significant PC was not detected on MRI. When using the PI-RADS classification, extensive T2w changes and DCE led to a classification in category 3, an observation that we made frequently in this cohort. The MRI appearance in these cases seem more likely to be age specific or inflammatory due to not PC-specific ADC values, but nonetheless PC cannot be excluded safely. Patient summary: Magnetic resonance imaging characteristics in young healthy men with normal prostate-specific antigen levels are, in particular, diffuse T2-weighted hypointensity and dynamic contrast enhancement of the peripheral zone. These seem to be more likely age specific or inflammatory, but resulted in a higher proportion of patients with Prostate Imaging Reporting and Data System 3 classification.